Human Circulating and Tissue-Resident CD56bright Natural Killer Cell Populations - Melsen, Janine E.; Lugthart, Gertjan; Lankester, Arjan C.; Schilham, Marco W. (Frontiers in Immunology, 2016)
Two human natural killer (NK) cell subsets are usually distinguished, displaying the CD56dimCD16+ and the CD56brightCD16-/+ phenotype. This distinction is based on NK cells present in blood, where the CD56dim NK cells predominate. However, CD56bright NK cells outnumber CD56dim NK cells in the human body due to the fact that they are predominant in peripheral- and lymphoid tissues. Interestingly, within the total CD56bright NK cell compartment, a major phenotypical and functional diversity is observed, as demonstrated by the discovery of tissue-resident CD56bright NK cells in the uterus, liver and lymphoid tissues. Uterus-resident CD56bright NK cells express CD49a, while the liver- and lymphoid tissue-resident CD56bright NK cells are characterized by co-expression of CD69 and CXCR6. Tissue-resident CD56bright NK cells have a low natural cytotoxicity and produce little interferon-γ upon monokine stimulation. Their distribution and specific phenotype suggest that the tissue-resident CD56bright NK cells exert tissue-specific functions. In this review, we examine the CD56bright NK cell diversity by discussing the distribution, phenotype and function of circulating and tissue-resident CD56bright NK cells. In addition, we address the ongoing debate concerning the developmental relationship between circulating CD56bright and CD56dim NK cells and speculate on the position of tissue-resident CD56bright NK cells. We conclude that distinguishing tissue-resident CD56bright NK cells from circulating CD56bright NK cells is a prerequisite for the better understanding of the specific role of CD56bright NK cells in the complex process of human immune regulation.